The role of women in preserving local wisdom Poda Na Lima 'Five Advices of Cleanliness' for the community health in Toba Batak at Lake Toba area - Robert Sibarani; Peninna Simanjuntak; Echo J. Sibarani (Elsevier, 2021)
Objective: This study aimed at (1) describing the local wisdom Poda Na Lima 'Five Advices of Cleanliness' for community health, and (2) analyzing the local women's activities in preserving the local wisdom Poda Na Lima 'Five Advices of Cleanliness' for the community health in Toba Batak. Method: The research method employed in this study was qualitative paradigm with interactive model in four interactive steps. After data collection, there were three steps of analysis, namely data display, data condensation and conclusion drawing/verification. The interactive model of the research method was conducted with anthropolinguistic approach. Results: Toba Batak has inherited and practiced local community Poda Na Lima 'Five Advices of Cleanliness' for community health, which is very important to be continuously practiced to keep healthy such as on this Covid-19 pandemic. Toba Batak women conduct healthy activities to ask and guide people to keep clean and stay healthy. Conclusion: Women play a significant role to preserve local wisdom Poda Na Lima 'Five Advices of Cleanliness' for keeping clean and stay healthy.